Enhancing plant resilience: arbuscular mycorrhizal fungi’s role in alleviating drought stress in vegetation concrete - Guo, Shiwei; Xia, Lu; Xia, Dong; Li, Mingyi; Xu, Wennian; Liu, Liming (Frontiers in Plant Science, 2024)
Drought stress usually inhibits plant growth, which may increase the difficulty of greening slopes. In this study, we systematically investigated the effects of arbuscular mycorrhizal (AM) fungi on the growth and drought tolerance of two plant species, Festuca elata and Cassia glauca, in a vegetation concrete environment by exogenously inoculating AM fungi and setting three drought levels: well water, moderate drought and severe drought. The results showed that plant growth was significantly inhibited under drought stress; however, AM fungi inoculation significantly promoted increases in plant height, root length, and above-and belowground biomass in these two plant species. Compared with, those in the CK treatment, the greatestAfter inoculation with AM fungi, the highest observed increases in the net photosynthesis rate, stomatal conductance and transpiration rate in the AM treatment group were 36.72%, 210.08%, and 66.41%, respectively, compared to CK. Moreover, inoculation with AM fungi increased plant superoxide dismutase and catalase activities by 4.70-150.73% and 9.10-95.70%, respectively, and reduced leaf malondialdehyde content by 2.79-55.01%, which alleviated the damage caused by oxidative stress. These effects alleviated the damage caused by oxidative stress and increased the content of soluble sugars and soluble proteins in plant leaves by 1.52-65.44% and 4.67-97.54%, respectively, which further increased the drought adaptability of plants. However, inoculation with AM fungi had different effects on different plants. In summary, this study demonstrated that the inoculation of AM fungi in vegetation concrete environments can significantly increase plant growth and drought tolerance. The plants that formed a symbiotic structure with AM fungi had a larger root uptake area, greater water uptake capacity, and greater photosynthesis and gas exchange efficiency. In addition, AM fungi inoculation further increased the drought adaptability of the plants by boostingincreasing their antioxidant enzyme activitiesy and regulating their metabolite content. These findings are highly important for promoting plant growth and increasing drought tolerance under drought conditions, especially for potential practical applications in areas such as slope protection, and provide useful references for future ecological engineering and sustainable development.